The Internationalization of U.S. High Schools: Avenues for Future Research - Nicola, Tara (Journal of International Students, 2021)
Although the internationalization of the U.S. education sector is perhaps the most salient at the postsecondary level, U.S. secondary schools have increasingly experienced the effects of globalization. In recent years, these schools have witnessed a surge in their population of international students. However, there is relatively little scholarship focused on this student population. This Research in Brief article first highlights recent research on nonimmigrant, international high school students in the United States. Using Bronfenbrenner’s (1977) ecological systems theory as a framework, the article then identifies areas where future research is needed to more fully explicate the unique experiences of these students and their effects on the U.S. secondary education sector.